Quantifying the Trade and Welfare Effects of EU Aflatoxin Regulations on the Dried Fruit Industry - B. Mug̈e Vural; E. Sedef Akgun̈gor̈ (German Journal of Agricultural Economics (GJAE), 2019)
Increased concerns on food contaminants draw special attention to food safety regulations. These regulations may have direct impact on food trade. The aim of the paper is to assess the impact of regulations concerning aflatoxin maximum residue limits (MRL) on dried fruits trade. The empirical method we adopt combines both gravity and welfare methodologies in a partial equilibrium context.
Keywords: 330